2021
DOI: 10.1108/ijot-11-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of occupational therapy interventions in the treatment of people with substance use disorders

Abstract: Purpose Diagnosis of substance use disorders and addictive behaviours are growing worldwide. It is timely to examine and collate literature on the nature of occupational therapy intervention in this field, to increase understanding of current practice and inform future directions. The purpose of this paper is to source and synthesise literature on occupational therapy interventions used in the treatment of people experiencing addiction. Design/methodology/approach Four databases were searched in August 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The intervention is therefore important in changing the habits and routines of clients' lifestyles to maintain and restore roles they lost because of substance use 12 . Ryan and Boland 13 support the understanding that occupational therapy is well-positioned to treat substance users and is most effective and supportive when going beyond teaching of skill to prioritise occupational engagement and client-centered practice.…”
Section: Introductionmentioning
confidence: 93%
“…The intervention is therefore important in changing the habits and routines of clients' lifestyles to maintain and restore roles they lost because of substance use 12 . Ryan and Boland 13 support the understanding that occupational therapy is well-positioned to treat substance users and is most effective and supportive when going beyond teaching of skill to prioritise occupational engagement and client-centered practice.…”
Section: Introductionmentioning
confidence: 93%
“…Research indicates that individuals with SUDs should receive interdisciplinary care, including occupational therapy, that is prepared to treat the multi-faceted and complicated nature of SUDs. 9 , 10 In occupational therapy, SUDs are most often treated as a co-occurring disorder, leading to a focus primarily on referral for physical, psychological, or social problems secondary to the misuse of substances. 11 Today’s best practice indicates that to properly treat these clients, occupational therapists need to understand current evidence-based practice within their scope and understand and implement a Screening, Brief Intervention, and Referral to Treatment (SBIRT) Model.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“… 12 , 13 Unfortunately, in the profession, there is also limited up-to-date research and practice in this area. In Amorelli’s 9 narrative review on occupational therapy interventions for SUDs, only 10 articles met the criteria for further analysis and in Ryan and Boland’s 10 scoping review, an additional 8 were identified. Additionally, occupational therapists are not assessing for SUDs frequently, despite the profession’s ability to be instrumental in the earlier detection and treatment of the disorder.…”
Section: Background/literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As I review through the five articles for this edition, it strikes me how our profession has embraced a mix of methods to address gaps in knowledge and/or practise relevant to occupational therapy. Firstly, Yoo (2023) effectively applies scoping review methodology to map the evidence on sleep interventions in mental health, a great example of this popular form of review structure being used to explore an area of clinical relevance to occupational therapy. Examples of cross-sectional survey work include illuminating about student knowledge and attitudes towards older adults with dementia (Gavin et al , 2023), as well as investigating which outcome measures are used by occupational therapy staff in adult social care settings in the UK (Davenport and Underhill, 2023), who interestingly using social media as primary way of recruiting participants.…”
mentioning
confidence: 99%